Acute effect of edge-to-edge repair of mitral regurgitation on left heart mechanics and health status. Issue 12 (17th December 2022) - Ro, Richard; Prandi, Francesca R.; Zaid, Syed; Anastasius, Malcolm O.; Tang, Gilbert H.L.; Seetharam, Karthik; Argulian, Edgar; Massaro, Gianluca; Sharma, Samin; Kini, Annapoorna; Lerakis, Stamatios
Abstract : Aims: Examine the impact of acute changes in left heart strain and volumes with percutaneous edge-to-edge MitraClip repair on improvement in health status assessed using Kansas City Cardiomyopathy Questionnaire-12 (KCCQ-12) score. Methods: Changes in left atrial strain, left ventricular (LV) global longitudinal strain (LVGLS), LV end-systolic volume (LVESV), and end-diastolic volume (LVEDV) were evaluated in 50 patients undergoing MitraClip repair for symptomatic primary mitral regurgitation (PMR) and secondary mitral regurgitation (SMR) on transthoracic echocardiography before and 1 month after MitraClip. Multivariable regression was used to evaluate changes in left heart strain and volumes as predictors of change in KCCQ-12 scores, adjusting for baseline clinical and echocardiographic characteristics. Results: Both PMR and SMR patients had significant increase in LVGLS and reduction in LVEDV and LVESV ( P  < 0.05) after MitraClip, reduction trend in left atrial conduit strain (PMR P  = 0.053; SMR P  = 0.12) but no significant change in LV ejection fraction. KCCQ-12 score improved significantly in both PMR ( P  < 0.001) and SMR cohorts ( P  < 0.001). Higher delta KCCQ-12 tertiles were associated with greater reduction in LVEDV ( P  = 0.022) after MitraClip. On multiple regression analysis, lower preprocedural Society of Thoracic Surgeons for Mitral Valve Replacement and KCCQ-12 score, and greater reduction in LVESV and left atrial strain conduit phase were associated with KCCQ-12 score improvement ( P  < 0.001). Conclusion: There is a significant increase in LVGLS and reduction in LVEDV, LVESV and left atrial strain conduit after edge-to-edge MitraClip repair in both PMR and SMR. Lower preprocedural Society of Thoracic Surgeons for Mitral Valve Replacement and KCCQ-12 score, and greater reduction in LVESV and left atrial conduit strain were associated with KCCQ-12 score improvement after MitraClip. Further studies are warranted to understand the mechanism and significance of our findings.